Complexity of Agrarian Law Regulations in Disputes over Unauthorized Use of Land - Dedy Cahyadi; Ade Saptomo (Yayasan Adra Karima Hubbi, 2024)
Background: The complexity of agrarian law regulation in Indonesia has led to significant legal uncertainty and social conflicts, particularly regarding unauthorized land use. Land, as a vital resource in agrarian societies, often becomes the center of disputes due to ineffective land administration, the misuse of land certificates, and corrupt practices. Objective: This study aims to analyze the challenges in agrarian law regulation and propose measures to address disputes over unauthorized land possession. Methodology: Using a normative legal research method, this study examines relevant regulations, including Law No. 5 of 1960 on the Basic Agrarian Law, through legislative and conceptual approaches. Findings: The research identifies key challenges, such as inefficiencies in land administration, abuse of legal documentation, and systemic corruption. To resolve these issues, improvements in the land administration system, stricter enforcement of laws, and increased legal awareness among the public are necessary. Conclusion: The study concludes that more effective agrarian policies are essential to address disputes over unauthorized land use, ensuring legal certainty and minimizing conflicts.